Knowledge Transfer Experiences of Inpatriates in Multinational Companies - A Cognitive Dissonance Perspective - Schuster, Tassilo; Bernhard, Theresa; Jack, A. (Expatriates: Perspectives and Challenges of the 21st Century, 2019)
Inpatriates have become important means of knowledge transfer within multinational companies. Delegating foreign managers to the domestic management team enables MNCs to secure their long-term survival. But how can these employees be motivated to share their knowledge? In this exploratory study, we attempt to extract more information about knowledge transfer processes and inpatriates’ behavioral patterns. To provide a rich understanding of these processes from the inpatriates’ perspective, critical incidents reported by 22 inpatriates were content-analyzed. Using cognitive dissonance theory as theoretical framework, this study provides new insights about behavioral processes of inpatriates during their knowledge transfer experiences. The interview analysis reveals, for example, that inpatriates frequently exhibit dysfunctional behavior when they experience cognitive dissonance. Based on the results from this analysis, we deduce meaningful practical and theoretical implications for human resource departments and highlight directions for future research.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Cognitive dissonance theory; Conceptual study/qualitative study/exploratory study; Grounded theory approach; Inpatriate management; Inpatriates; Inpatriation; International assignments; Reputational asymmetry